Psalm 16 (LXX Ps 15) and Acts of the Apostles, part II - Groenewald, Alphonso (Old Testament essays, 2008)
Psalm 16 is one of the most well-known texts of the Psalter. This can be attributed to, amongst other things, the fact that the NT, specifically Acts of the Apostles, applied this text to the life of Jesus of Nazareth. The quotations from Psalm 16 in the book of Acts thus got a messianic-Christological meaning. If we, however, take a look at the text of Psalm 16, it seems that this psalm does not contain any direct messianic conceptions. Neither does it refer to the resurrection of the flesh. There are, however, features in the Greek translation (LXX) of this psalm which offered material to the New Testament authors to apply the text to Jesus - specifically to his resurrection from death. In Part I of this article the focus was on the MT text of Psalm 16. Part II will focus on its application in Acts of the Apostles, as well as the hermeneutical background of the author(s) of Acts of the Apostles. It seems that the Septuagint paved the way for this interpretation of the MT text and that it can be regarded as 'praeparatio evangelica'.